(untitled) (Journal of the College of Basic Education, 2023)
This study aimed at identifying the educational effects resulting from Israeli military occupation checkpoints among students of Alaghwar schools passing though these checkpoints daily. More ever , to determine the impact of each of variables of sex ,qualification, years of experience , and to what extent do these effects differ. The population of study consisted of all teachers enrolled at Tubas directorate , these students who cross Israeli occupation forces barriers daily, From the main entrances of the district of Tubas these unmovable checkpoints. The researcher has chosen simple sample consists of (40) teachers from both sex . In order to achieve this , the researcher designed a questionnaire to measure the effects on student achievement resulting from Israeli Military Occupation Checkpoints . The researcher used a descriptive analytical approach and The study findings revealed the following: -The total mean value of the effects on student achievement resulting from the Israeli military occupation checkpoints among students of all the items and all the domains yielded (87%), this indicate that the effects of checkpoints were very high. - There were no statistically significant differences at (α=0.05) in the degree of educational effects resulting from Israeli Military occupation checkpoints among students between male and female . - There were no statistically significant differences at (α=0.05) in the degree of educational effects resulting from Israeli Military occupation checkpoints among students due qualification variable . - There were no statistically significant differences at (α=0.05) in the degree of educational effects resulting from Israeli Military occupation checkpoints among students due to place of residence . In the light of the finding of this study , the researcher recommends the following: 1-The necessity of activating the role of academic counseling (comprehensive) to face the educational effects resulting from the Israeli barriers. 2- The necessity of activating the e-learning development to meat the needs of students and academic outreach through electronic means